Firms' sustainability engagement and sustainability-related controversies - Peter Kotzian (Business Strategy and the Environment, 2023)
Sustainability issues became ever more important for firms' business strategies. Not living up to public and stakeholders' expectations results in controversies damaging the firm's reputation. Firms integrate sustainability aspects – environmental, social, and governance (ESG) issues – in their business strategies to satisfy stakeholders ranging from customers to investors. Substantial resources are invested to increase their sustainability engagement to avoid sustainability-related controversies. However, the degree to which sustainability engagement is effective is an open issue, as the occurrence of sustainability-related controversies has structural components, which are under the firms' control, but also random components. Using data on firms' sustainability engagement, this paper investigates to what degree firms can actually avoid controversies by engaging in sustainability and to what degree such controversies are caused by factors beyond the firm's control, like random events or the societal environment. Our findings indicate strong sustainability engagement to be a significant factor for avoiding controversies, albeit the magnitude of the effect is very limited. While controversies are not purely random events, they are driven strongly by factors beyond the firm's strategic control, like firm size and country of origin.
Keywords: 330; corporate reputation; environmental policy; ESG performance; stakeholder engagement; stakeholder management; sustainability engagement; sustainability performance